Analisis Sistem Tanda di Ramayana Teladan Medan : Kajian Semiotik Charles Sanders Peirce - Nia Khairunnisa; M. Sholeh Sihombing; Cantika Mawarni; Christian Sinaga (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
The sign system in public spaces functions as a visual communication tool and shapes people's experiences and perceptions. The objectives of this study are; 1) to identify the types of signs found in shopping centers; 2) to analyze the function and role of these signs in supporting activities and social interactions in shopping centers; and 3) to explain how these signs influence visitors' perceptions and experiences. The research method used is descriptive qualitative with research stages including literature study, determining the location of the study, data collection, data analysis using Peirce's semiotic theory, data validity testing, and drawing conclusions. Data collection techniques are carried out through observation and documentation stages. The results of this study found that the visual sign system in the Ramayana Teladan Medan shopping center is classified into several categories of signs according to Charles Sanders Peirce's semiotic theory, such as Rhematic Indexical Legisign, Dicent Sinsign, Qualisign, and Iconic Legisign. Visualization of signs—whether through images, colors, or text—can influence visitors' understanding and behavior, for example by increasing alertness, compliance with rules, or perceptions of safety and comfort.